ANALYSIS AND DESIGN REINFORCED CONCRETE CONSTRUCTION STRUCTURE OF 4 FLOOR HOTEL IN KUNINGAN - Roesdiana, Tira; Perdana, Renaldi Indra (Journal of Green Science and Technology, 2023)
Planning for a 4-storey hotel in Kuningan is projected to support supporting facilities for the tourism sector in Kuningan Regency, supporting facilities like this are really needed by Kuningan Regency which has great potential in the tourism sector and is proven by the continuing increase in the number of tourists every year, with the development of Kuningan Regency and the increasingly widespread the construction of multi-storey buildings is needed planning in order to make efficient use of land. To support the availability of tourism support facilities, this research will examine the planning of hotel building structures based on SNI 2847-2019, SNI 1727-2020 and SNI 1726-2019 and calculate the budget plan for the structural work. Referring to these rules, the dimensions of the structural elements and the need for structural reinforcement can be produced that meet the rules and can also support the work force and loads received on a building including earthquake loads, wind loads and rain loads. The cost of building a 4-storey hotel building in this study is Rp. 26,712,400,000.00 (Twenty Six Billion Seven Hundred Twelve Million Four Hundred Thousand Rupiah), and the cost of building a one square meter building is Rp. 4,345,716.00 (Four million three hundred forty-five million seven hundred and sixteen thousand rupiah).